Enhancing Service Quality In Tourism Through Artificial Intelligence: A Study Of Private Hospitality Services In Uttar Pradesh (International Journal of Environmental Sciences, 2025)
The hospitality industry is increasingly incorporating technological advancements to improve service quality, enhance guest satisfaction, and streamline operations. In recent years, Artificial Intelligence (AI) and Machine Learning (ML) have emerged as pivotal tools in optimizing guest experiences and operational efficiency. This paper explores the integration of AI and ML technologies within private hospitality services in Uttar Pradesh, focusing on their impact on service quality dimensions such as responsiveness, reliability, personalization, and operational efficiency. By adopting AI-driven systems for personalized guest experiences, predictive maintenance, and automated interactions, hospitality services can significantly elevate their service offerings. This study employs a mixed-methods research approach, combining qualitative interviews with hospitality managers, staff, and guests, alongside quantitative surveys that assess the efficacy of AI systems in improving service delivery. Findings indicate that AI technology can enhance guest satisfaction by as much as 20%, particularly in areas related to personalization and operational efficiency. However, the implementation of these technologies is not without challenges, including high costs, data privacy concerns, and the need for skilled labor. This paper provides an in-depth analysis of these opportunities and challenges and offers recommendations for hospitality providers in Uttar Pradesh to leverage AI and ML for superior service quality.